Im Kwon-Taek - Chŏng, Sŏng-il 1959- (Korean film directors., 2006)
"The history of modern Korea consists of many fetters, in which different generations live with very different experiences. Many artists left records rof their generations but Im Kwon-Taek is the only one who has truly embraced all the events of the 20th century and is conveying a message to us now. Just looking at the results, he is nearly the most miraculous survivor but when the personal story of his survival comes to light, the miracle is a record of the tears of a tragic history. Describing Im Kwon-Taek is recording the history of Korean movies and furthermore, explaining the history of modern Korea."--Back cover.